STUDI EVALUASI SISTEM BANGUNAN PELIMPAH PADA BENDUNGAN GRAWAN KABUPATEN REMBANG PROVINSI JAWA TENGAH - Aini Amalia, Ayu Khurotul; Asmaranto, Runi; Priyantoro, Dwi (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2019)
Setelah adanya kegiatan inspeksi pada Bendungan Grawan, diperlukan adanya evaluasi terhadap sistem bangunan pelimpah. Evaluasi disesuaikan dengan kondisi eksisting dengan As Built Drawing menggunakan analisa hidrologi, hidrolika dan stabilitas bangunan. Selanjutnya adalah mengusulkan rencana perbaikan dari hasil evaluasi dengan pertimbangan hidrologi, hidrolika dan stabilitas (guling, geser, eksentrisitas dan daya dukung tanah). Dalam studi ini juga akan menganalisa mengenai kavitasi, analisa aliran getar dan perkiraan kedalaman gerusan.Dari hasil studi didapatkan hasil analisa berupa usulan perbaikan untuk panjang peredam energi vlugter, panjang saluran transisi, peredam energi dan perlindungan terhadap dasar saluran pengarah hilir dari bahaya gerusan dengan menggunakan rip-rap. Selanjutnya merencanakan bentuk dinding penahan yaitu menggunakan dinding penahan tipe gravity wall. Setelah dilakukan analisa untuk stabilitas guling, geser dan eksentrisitas pada ambang pelimpah dan dinding penahan memenuhi persyaratan untuk kondisi normal > 1,5 dan kondisi gempa > 1,2. Daya dukung tanah pada ambang pelimpah dan dinding penahan dapat menahan tegangan yang terjadi pada bangunan. After inspection of the Grawan’s Dam, an system of spillway evaluation is required. The assessment is adapted to existing conditions using As Built Drawing related to hydrological, hydraulics and stability analysis. Furthermore, a plan to improve the evaluation results in consideration of hydrology, hydraulics and stability (overturning, sliding, eccentricity and bearing capacity) will be proposed. This study also analyzes cavitation, pulsating flow analysis and scouring depth.From the results of the investigation, the results of the analysis were presented in the form of suggestions for improvement of the length of the Vlugter, the length of the transitional channel, stilling basin and the protection of escape channel by using Rip-Rap. The next step is a plan of the retaining wall with a gravity wall. Shear and eccentricity for spillway and retaining wall meet the requirements for normal conditions> 1.5 and earthquake conditions> 1.2 after analysis of the roll stability. However, the bearing capacity of spillway and retaining walls can overcome the stress of the buildings.After inspection of the Grawan’s Dam, an system of spillway evaluation is required. The assessment is adapted to existing conditions using As Built Drawing related to hydrological, hydraulics and stability analysis. Furthermore, a plan to improve the evaluation results in consideration of hydrology, hydraulics and stability (overturning, sliding, eccentricity and bearing capacity) will be proposed. This study also analyzes cavitation, pulsating flow analysis and scouring depth.From the results of the investigation, the results of the analysis were presented in the form of suggestions for improvement of the length of the Vlugter, the length of the transitional channel, stilling basin and the protection of escape channel by using Rip-Rap. The next step is a plan of the retaining wall with a gravity wall. Shear and eccentricity for spillway and retaining wall meet the requirements for normal conditions> 1.5 and earthquake conditions> 1.2 after analysis of the roll stability. However, the bearing capacity of spillway and retaining walls can overcome the stress of the buildings.